TRANSCATHETER AORTIC VALVE IMPLANTATION IN PATIENTS WITH LEFT ATRIAL APPENDIX THROMBUS - Hüseyin Ayhan; Tahir Durmaz; Telat Keleş; Abdullah Nabi Aslan; Cenk Sarı; Hacı Ahmet Kasapkara; Emine Bilen; Nihal Akar Bayram; Murat Akçay; Engin Bozkurt (Российский кардиологический журнал, 2014)
Aim. The transcatheter aortic valve implantation (TAVI) which developed in the recent years has become an alternative for surgery. However, in spite of new developments the process based vascular and neurological complications still remain to be a problem with elderly patients who also tend to have many co-morbid conditions. With this study we aimed to evaluate the TAVI efficacy and reliability on patients with scarcely relative contraindication and with intracardiac thrombus who are mostly left out of the study.Methods and Results. There has been a successful TAVI process conducted in our clinic for antiplatelet and anticoagulation for 6 cases in which thrombus was seen in left atrial appendix (LAA) via transesophageal echocardiography (TEE) and which are not suitable for surgical valve replacement due to atrial fibrillation (AF) and severe AS comorbid reasons. Edwards SAPIEN XT valve was implanted to all patients transfemorally with general anaesthesia. The process was facilitated successfully and no major/minor stroke was observed in post-process early period, and 9 month controls, in average.Conclusion. Other than AS, also AF, whose frequency increases with age, is an important risk factor for neurological complications. In patients who has AF and AS the source of the cardioembolic focus is mainly LAA. The post-TAVI antiplatelet and anticoagulation treatment is not clear for these patients. We tried to show that TAVI process is reliable in terms of the risk of stroke, in careful processing and suitable anticoagulation treatment for the patients with AF, AS and LAA in this first case study in literature, as far as we know.